177k views
2 votes
(2x+5)(x-4)=0 in standard form and value of a,b, and c

User Dronus
by
5.0k points

2 Answers

5 votes

hi

A = (2x+5)(x-4)=0

A = 2x²-8x +5x-20

A = 2x² -3x -20

as a quadratic equation is : ax² +bx +c

then a = 2 ; b = -3 and c = -20

User Yesilupper
by
5.2k points
6 votes

Answer:

a = 2 ; b = -3 ; c = -20

Step-by- step explanation:

Use FOIL method.

(2x + 5)(x - 4) = 0

2x*x+ 2x*(-4 )+ 5*x + 5* (-4) = 0

2x² - 8x + 5x - 20 =0

Combine like terms,

2x² - 3x - 20 = 0

Standard form: ax² + bx + x = 0

a = 2

b = -3

c = -20

(2x+5)(x-4)=0 in standard form and value of a,b, and c-example-1
User Bogdan Beda
by
5.5k points